Ointment of Ximenes americana promotes acceleration of wound healing in rats - Souza Neto Júnior,José de Castro (2019)
Abstract Purpose: To evaluate the healing potential of the Ximenia americana hydroalcoholic extract in 10% cream in excisional wound models in rats. Methods: Sixty male adults Wistar rats were submitted to skin and subcutaneous tissue surgery in the right and left thoracic regions, divided into three experimental groups: Standard submitted to treatment with only the base vehicle, Treated wounds treated with hydroalcoholic extract of X. americana applied on 10%, Lanette base and Control, untreated wounds. The treatment was performed daily and the wounds evaluated microscopically by the quantification of fibroblasts, collagen fibers and blood vessels. Results: The histomorphometric analysis showed a significant increase in the number of fibroblasts, collagen fibers and blood vessels in the treated group. Conclusion: The topical action of the cream based on Ximenia americana shows angiogenic effects and improves the replacement of collagen, suggesting its use for the development of herbal remedy in the treatment of cutaneous wound healing.